Association of interleukin-6 gene polymorphisms with the risk of hepatocellular carcinoma: An up-to-date meta-analysis. Issue 50 (11th December 2020) - An, Pei-Pei; Feng, Li-Na; Zhang, Xiao-Xue; Jin, Qing-Long
Abstract: Background: This study was aimed to evaluate the association between interleukin-6 (IL-6) gene polymorphisms and the risk of hepatocellular carcinoma (HCC) in a meta-analysis. Methods: A literature search was performed for case-control studies published during May, 1993 to May, 2020 focusing on IL-6 gene polymorphisms (–174G > C, –572G > C, and –597G > A) and HCC susceptibility by using PubMed, Cochrane Database, EMBASE, Web of science, and China National Knowledge Infrastructure. From 128 full-text articles, 11 were included in this meta-analysis. I 2 index was used to assess heterogeneity and Newcastle-Ottawa Scale was utilized for quality assessment. Results: For IL-6 –174G > C polymorphism, in codominant (GG vs CC: odds ratios [OR] = 2.78, 95% confidence intervals [CI] = 1.25–6.19, P  = .01, I 2  = 16%) and recessive (GG+GC vs CC: OR = 2.76, 95% CI = 1.29–5.90, P  = .009, I 2  = 3%) models, IL-6 –174G>C polymorphism was significantly associated with the risk of HCC. In dominant (GG vs CC+GC: OR = 1.80, 95% CI = 0.92–3.54, P  = .09, I 2  = 86%) and allele (G vs C: OR = 1.49, 95% CI = 0.95–2.32, P  = .08, I 2  = 68%) models, IL-6 –174G>C polymorphism had no impact on the risk of HCC. However, in non-Italian Caucasian population, IL-6 –174G>C polymorphism was significantly related to the occurrence of HCC in both dominant (GG vs CC+GC: OR = 3.26, 95% CI = 2.29–4.65, P  < .00001, I 2  = 0%) and allele (G vs C: OR = 2.48, 95% CI = 1.48–4.15, P  = .0006) models. Such correlations also could be observed when healthy individuals were selected as controls. For IL-6 –572G>C and –597G>A polymorphisms, no significant association was observed in all models, regardless of the source of control and population subgroups. No publication bias could be calculated when Begg and Egger tests were employed. Conclusion: This meta-analysis indicated that IL-6 –174G>C polymorphism was significantly related with the risk for HCC, especially in non-Italian Caucasian population. No significant association was observed for the correlation between IL-6 –572G>C and –597G>A polymorphisms and HCC susceptibility. Abstract : Supplemental Digital Content is available in the text